Typologies of Islamic Religious Parenting in Yogyakarta: Intensive, Supplemental, and Laissez-Faire Patterns Shaping Children’s Spiritual Development - Maksudin; Imam Machali; Sudiati; Zawawi Ismail (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study aims to explore patterns of Islamic religious parenting within Muslim families in Yogyakarta, focusing on three typologies of parental involvement intensive, supplemental, and laissez-faire and their impact on children's spiritual development. The study seeks to contribute to understanding how different parenting styles influence children's religious formation and spiritual identity. Design/methods/approach – A qualitative case study design was employed, using semi-structured interviews and non-participant observations as the primary data collection methods. Five purposively selected parents were involved in the study, providing insights into their approaches to religious education within the family context. The data were analyzed using thematic analysis to identify key patterns and themes. Findings – The study found that intensive parenting promotes a deep internalization of religious values through consistent rituals, modeling, and emotional engagement. In contrast, supplemental parenting offers situational reinforcement but lacks routine and depth. The laissez-faire model, which emphasizes autonomy, often results in fragmented or superficial religious formation due to minimal parental involvement. These findings highlight the crucial role of home-based religious education in shaping a child’s spiritual identity. Research implications/limitations – The study’s limitations include its small, localized sample, which may not be generalizable to broader contexts, and the absence of children’s perspectives, which could provide a more comprehensive view of religious parenting dynamics. The findings suggest the need for community-driven programs to enhance parents’ religious and pedagogical competencies. Originality/value – This research provides valuable insights into the diverse ways in which Muslim parents in Yogyakarta engage with religious education, with implications for improving parental involvement in children's spiritual development. Future research should explore broader demographics and adopt longitudinal designs to better understand the evolving nature of religious parenting.